How teenagers continue school after a diagnosis of cancer: experiences of young people and recommendations for practice. (December 2016) - Pini, Simon; Gardner, Peter; Hugh-Jones, Siobhan
Aim: To understand how teenagers experience school following a diagnosis of cancer, and to offer recommendations for practice.Methods: Using visual interviewing at three time points, 12 participants (13–16 years) from England discussed school experiences during the year following their diagnosis. Interpretative phenomenological analysis provided in-depth assessment of their individual experiences.Results: One main theme emerged: regulation and calibration. Remaining engaged in school allowed teenagers to maintain noncancer versions of themselves as well as incorporating new cancer experiences. Six subthemes emerged: examinations/grading, school community, miscommunications, peers, altered appearances and normality.Conclusion: A total of 13 recommendations are offered for the development of education support to young people with cancer, covering the role of the school, the young person and their peers, flexibility and timing.